Respon Guru dan Peserta Didik terhadap Perangkat Pembelajaran Berbasis Pendekatan Konflik Kognitif dalam Model Blended Learning - Martina Nur Larasafitri; Gunawan Gunawan; Kosim Kosim; Lovy Herayanti (Indonesian Journal of STEM Education, 2023)
This research aims to determine the response of teacher and students to learning device based on the cognitive conflict approach in the blended learning model. This learning device was developed to improve students' mastery of concepts and critical thinking skills. This research was carried out at SMA Negeri 6 Mataram. The learning tools developed are learning plans (RPP), learning materials, LKPD (students worksheets), and evaluation instruments. The subjects of this research were a physics teacher at SMA Negeri 6 Mataram and students in class XI MIA 4. The responses of teachers and students were part of a practical analysis. The data collection instrument was a questionnaire. Teachers and students were given questionnaires to respond to the learning tools developed. The teacher responds to the entire device while the students respond to the learning process, learning materials and LKPD that they study. The results of the analysis show that the learning tools are categorized as practical. This means that the learning tools developed can be used in learning. A more complete and detailed explanation of these results is presented in this article.